Resistance Patterns and Patient Characteristics as Predictors of Treatment Outcomes in Drug-Resistant Tuberculosis: Evidence from a District TB Centre in Western Maharashtrace from a District TB Centre in Western Maharashtra (GAIMS Journal of Medical Sciences, 2026)
Background: The emergence & dissemination of Drug-Resistant Tuberculosis (DR-TB) pose one of the most formidable public health challenges that threaten to undermine global TB control efforts. While the national and state-level data on DR-TB are available, detailed district-level analyses are limited. This study was conducted to fill this knowledge gap and provide insights into the demographic characteristics, resistance patterns, and treatment outcomes of DR-TB patients, specific to the local population, which can help to inform policy decisions and improve the patient management strategies. Objectives: 1) To determine the proportion of DR-TB among microbiologically confirmed TB cases, 2) To evaluate patient characteristics, drug resistance patterns, and treatment outcomes in DR-TB patients, and 3) To analyze the correlations between treatment outcomes, patient characteristics, and resistance patterns to identify predictors of treatment success or failure. Material and methods: A retrospective analysis of data was conducted from the NIKSHAY portal, focusing on DR-TB patients registered at the District Tuberculosis Centre, Kolhapur, Western Maharashtra. Patient demographics, clinical characteristics, drug resistance profiles and treatment outcomes were extracted and analyzed. Multivariate logistic regression identified outcome predictors. Results: The proportion of DR-TB patients among all the Microbiologically confirmed cases was found to be 10.05%. The majority of patients were males (61.36%) and belonged to 18-59 years age group (79.7%). Based on BMI, 59.90% belonged to the underweight category. Maximum patients i.e. 48.16% had MDR/RR-TB, followed by 32.51% H-monoresistance and 19.31% Pre-XDR cases. Out of 296 DR-TB patients whose outcome was available, 71.96% achieved successful treatment outcomes. 15.54% of these 296 cases had died. Conclusion: Adults in the economically productive age group (18-59 years), males & underweight people were commonly affected. MDR-TB was found to be the leading form of DRTB. Patients under 18 years, Males, patients with pulmonary TB, HIV-reactive patients, underweight patients, Pre-XDR pattern, had higher odds of unsuccessful outcomes.